צלת א-שקאוף - Buzakhar, Madghis (עיתון קהילת יהודי לוב, 2010)
(Tzallat A-Shqaouf)." ERA (Journal de la communauté juive de Libye), n° 126 (Septembre-Octobre 2010): 26.
Keywords: Judaïsme – Djebel Nefousa

Le destin d’une communauté méditerranéenne. Les mémoires privées des juifs libyens - Lucia Sergio, Marialuisa (EnJeu, 2017)
Keywords: Judaïsme – Djebel Nefousa

Yefren - Roumani, Maurice (Encyclopedia of Jews in the Islamic World, 2010)
Keywords: Judaïsme – Djebel Nefousa

Jebel Nafusa - Simon, Rachel (Encyclopedia of Jews in the Islamic World, 2010)
Keywords: Judaïsme – Djebel Nefousa

Gharian - Roumani, Maurice (Encyclopedia of Jews in the Islamic World, 2010)
Gharian is a town in northwestern Libya about 80 kilometers (50 miles) south of Tripoli in the Nafusa Mountains. It is considered to constitute a single unit with the nearby towns of Tighrinna and Banu Abbas. All three towns had Jewish inhabitants, but most of them lived in Tighrinna, just south of Gharian, which was referred to variously as ḥārat al-yahūd (the Jewish Quarter) and arḍ al-yahūd (Jewish Land). Gharian town had the smallest Jewish population of the three settlements. According to the 1944 census there were ninety Jews in Gharian, 343 in Tighrinn…
Keywords: Judaïsme – Djebel Nefousa

The Names of the Jews of Lybia During the Italian Occupation : Gender, Society, and Culture - Henshke, Yehudit (La Rassegna mensile di Israel, 2017)
Keywords: Judaïsme – Djebel Nefousa

Uccideteli tutti: Libia 1943: gli ebrei nel campo di concentramento fascista di Giado : una storia italiana - Salerno, Eric (Il Saggiatore, 2012)
Keywords: Judaïsme – Djebel Nefousa

Letters of medieval jewish traders - Goitein, S. D (Princeton University Press, 2016)
Keywords: Judaïsme – Djebel Nefousa